Effects of Eutrophication on Ogbuamuma River in Emeabiam Community, Owerri West Local Government Area - Okere, Chibueze Sylvester; Anuniru, Chinazom Onyekachi; Awurum, Ivy Ihuaku; Onyeanuna, Ngozi Ihechiluru; Nzewuihe, Victory Obum; Bright, Hilda; Nwagbara, Chinedu Evarestus (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
The current study aims to assess factors contributing to eutrophication in the Ogbuamuma River in the Emeabiam community in Owerri West local government area of Imo state which is not exempt from the pervasive issue of eutrophication, a process exacerbated by anthropogenic activities such as urbanization, agricultural runoff, and industrial discharges. The surface water samples were collected from three sample points in the upstream to the downstream direction and screened for selected parameters such as temperature, colour, pH, turbidity, dissolved oxygen, total dissolved solids, biological oxygen demand, total suspended solids, and nitrates using standard methods. The colour and turbidity were reported to be muddy, and the pH of the studied surface water was acidic with mean values of 5.30 to 5.78. Total dissolved solids were all below the acceptable limit of 500 mg/l, but total suspended solids were all over the permissible limit of 10 mg/l with the highest value of 40.50 mg/l. Additionally, there was a surge of nitrate levels from 21.60 mg/l – 40.20 mg/l and low values of dissolved oxygen from 4.30 mg/l – 6.75 mg/l across the sample points. The river bank is surrounded by densely populated human settlements and agricultural fields. Sewage from the households and the runoff brings down fertilizers and other chemicals from household and agricultural fields into the river water. To optimize nutrient concentration reductions, particularly during the year's rainy season, it is crucial to address point sources in their entirety where they can be used by rooted plants and benthic algae.